Effects of phosphorus-modified biochar as a soil amendment on the growth and quality of Pseudostellaria heterophylla - Charles Wang Wai Ng; Yu Chen Wang; Jun Jun Ni; Pui San So (Scientific Reports, 2022)
Abstract Phosphorus (P) deficiency in agricultural soil is a worldwide concern. P modification of biochar, a common soil conditioner produced by pyrolysis of wastes and residues, can increase P availability and improve soil quality. This study aims to investigate the effects of P-modified biochar as a soil amendment on the growth and quality of a medicinal plant (Pseudostellaria heterophylla). P. heterophylla were grown for 4 months in lateritic soil amended with P-modified and unmodified biochar (peanut shell) at dosages of 0, 3% and 5% (by mass). Compared with unmodified biochar, P-modified biochar reduced available heavy metal Cd in soil by up to 73.0% and osmotic suction in the root zone by up to 49.3%. P-modified biochar application at 3% and 5% promoted the tuber yield of P. heterophylla significantly by 68.6% and 136.0% respectively. This was different from that in unmodified biochar treatment, where tuber yield was stimulated at 3% dosage but inhibited at 5% dosage. The concentrations of active ingredients (i.e., polysaccharides, saponins) in tuber were increased by 2.9–78.8% under P-modified biochar amendment compared with control, indicating the better tuber quality. This study recommended the application of 5% P-modified biochar for promoting the yield and quality of P. heterophylla.